Growth of Stipa breviflora does not respond to nitrogen addition because of its conservative nitrogen utilization - Zhao, Kun; Gao, Hui; Sun, Zhi; Zhang, Junling; Li, Haigang (Frontiers in Ecology and Evolution, 2023)
Enhanced atmospheric nitrogen (N) deposition is threating species diversity in the desert steppe ecoregions. Needlegrass (Stipa breviflora) is the dominant specie in the desert steppe grasslands of China and southern Mongolia, and the response of S. brevifolia to N deposition is not well known. In this study, we conducted an experiment to determine the growth and N uptake of S. breviflora in response to several N addition rates. The results showed that N addition did not change plant growth, emergence rate, plant height, or biomass of S. breviflora, even at a N addition rate of 50 kg N ha-1 yr-1 with sufficient soil moisture during a 120-day growth period. The absence of a N effect was due to the fact that N uptake in S. breviflora was not improved by N addition. These results indicated that S. breviflora is very conservative with respect to N utilization, which could possibly help it resist enhanced atmospheric N deposition. Moreover, conservative N utilization also enables S. breviflora to survive in N-limiting soils.